Comparison three primer pairs for molecular sex determination in Eurasian pygmy owls (Glaucidium passerinum) - Stehlíková Sovadinová, Simona; Mekadim, Chahrazed; Korpimäki, Erkki; Mrázek, Jakub; Kouba, Marek (Springer Nature, 2025)
Bird sex determination is fundamental in various ecological and biological studies, although many avian species cannot be sexed visually due to their monomorphic and/or monochromatic appearance. Thus, reliable laboratory methods for sexing are a prerequisite. Most avian nestlings lack sex-related signs, including the Eurasian pygmy owl (Glaucidium passerinum). We performed laboratory sex determination analysis of this species using blood samples of 242 juveniles and nine adults. It relied on the qPCR of the specific intron from the chromo-helicase DNA-binding protein 1 gene. We tested three primer sets, the P2/P8, 2550F/2718R, and CHD1F/CHD1R, commonly used for bird laboratory sexing. The outcomes were displayed on an agarose gel electrophoresis and a plot from melt curve analysis, which had not been previously conducted in Eurasian pygmy owls. We found that only primer set CHD1F/CHD1R proved reliable, as the only one determined sex with one and two band/s and peak/s on the electrophoresis and the melt curve plot for males and females, respectively. The other two primer pairs failed and depicted one band/peak in all specimens regardless of their sex. Therefore, we recommend performing Eurasian pygmy owls’ laboratory sexing by qPCR with CHD1F/CHD1R primers only.